Graphene active carbon-based material-loaded low-platinum catalyst as well as preparation method and application thereof
By loading platinum particles on graphene activated carbon-based materials, the mass transfer resistance and stability of platinum carbon catalysts in fuel cells are solved, and efficient oxygen reduction reaction and low-cost catalysts are achieved, which is suitable for a wide range of applications of fuel cells.
Patent Information
- Application Number
- CN202411322387.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-03
AI Technical Summary
The platinum carbon catalyst in existing proton exchange membrane fuel cells has problems such as increased mass transfer resistance, reduced stability and high cost caused by random distribution of Pt nanoparticles, which limits the widespread application of fuel cells.
Graphene activated carbon-based material is used as a support, and the oxygen reduction reaction performance and stability of the catalyst are improved by uniformly supporting platinum particles on the Co-N-C-G support, combining the high specific surface area and conductivity of graphene.
It significantly reduces the amount of platinum, improves the oxygen reduction performance and stability of the catalyst, and is suitable for large-scale production and the promotion of fuel cell technology.
Smart Images

Figure CN119252948A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a graphene active carbon-based material-supported low-platinum catalyst and a preparation method and application thereof, and belongs to the field of cathode catalytic materials for proton exchange membrane fuel cells. Background Art
[0002] With the country's strong support and development of clean and renewable energy, new energy sources such as hydrogen energy, wind energy, solar energy, and tidal energy have entered people's field of vision. As a new energy source, hydrogen energy can alleviate the intermittent and volatile problems of solar energy, wind energy, tidal energy, etc., and hydrogen fuel cells are efficient terminals that utilize hydrogen energy. As the reverse reaction of water electrolysis, the reaction product is water without any pollution. It can directly convert the chemical energy in hydrogen into electrical energy, which has great potential for solving energy and environmental problems.
[0003] The hydrogen economy, based on renewable energy sources such as hydrogen production, hydrogen storage and hydrogen power generation, is widely regarded as a promising solution for future energy. In the hydrogen economy, fuel cell vehicles (FCVs) are essential for low-carbon transportation. If fuel cell technology matures, greenhouse gas emissions from the transportation industry are expected to be reduced to near zero. Proton exchange membrane fuel cells (PEMFCs) are a relatively mature type of fuel cell. They have the characteristics of low operating temperature, easy operation, high energy density, and fuel diversity, and have broad application prospects. However, due to the high amount of platinum (Pt) and the slow kinetics of the cathode oxygen reduction reaction, there is currently a problem of high cost. Therefore, it is of great significance and urgency to develop low-Pt oxygen reduction catalysts with higher activity and stability, thereby effectively reducing the amount of Pt used in fuel cell stacks.
[0004] At present, commercial fuel cell catalysts are supported catalysts formed by randomly stacking Pt nanoparticles loaded on a carbon powder carrier, called platinum carbon catalysts. However, in practical applications, traditional platinum carbon catalysts have obvious disadvantages: first, the random distribution of Pt nanoparticles increases the resistance to the transmission of gas molecules and water molecules, affecting the mass transfer effect of fuel cells; second, Pt nanoparticles and carriers are bonded together by adhesives, which can easily cause nanoparticles to detach in complex environments, reducing the stability of the catalyst; third, since platinum is expensive, using platinum as a catalyst will greatly increase the cost of fuel cells, and therefore cannot be widely promoted.
[0005] The structure of the carbon support will affect the metal-support interaction of the catalyst. Liu et al. (Adv. Funct. Mater. 2018, 28, 1704537) found that the sp 2 The degree of hybridization will have a great influence on its electronic structure. 2The more hybridized carbon there is, the stronger the interaction with the Pt nanoparticles loaded on it. In addition, the defect structure on the carbon material will also affect its electronic structure, and these defects can provide stable anchoring points for the loaded metal, greatly improving the stability of the catalyst. As the number of defect structures on the carbon material increases, its work function gradually decreases, and the carbon material with more defects has a stronger electron transfer with the metal.
[0006] Graphene itself has a unique electronic structure and geometric structure, with a variety of doping and defect sites, high atomic utilization, and adjustable and stable structure. The theoretical specific surface area of graphene can be as high as 2600 m 2 g -1 , which is twice that of single-walled carbon nanotubes and much higher than most carbon black and activated carbon. This structural characteristic makes graphene a potential application prospect as a two-dimensional carrier for loading catalysts. Secondly, the unique local conjugated structure of graphene gives it a strong adsorption capacity for substrates in catalytic reactions. The superior electron mobility of graphene is also conducive to promoting electron transfer during catalytic reactions, which can effectively improve the catalytic activity of composite carbon carriers. Finally, graphene also has high chemical, thermal, optical and electrochemical stability. Its unique single-layer structure gives it a high surface energy, making it easier for nanoparticles to be adsorbed on its surface and making the nanoparticles more evenly dispersed, reducing agglomeration and effectively extending the service life of the catalyst.
[0007] Therefore, the present invention makes full use of the high specific surface area, high electronic conductivity, good thermal stability and corrosion resistance of graphene to design a novel activated carbon-based material-loaded low-platinum composite catalyst. Summary of the invention
[0008] The present invention aims to provide a graphene activated carbon-based material-supported low-platinum composite catalyst and a preparation method and application thereof. The catalyst particles prepared by the method are evenly dispersed, have an ideal particle size, and have high catalytic activity. The utilization rate of platinum in the catalyst can be improved, thereby significantly reducing the amount of platinum used. The stability of the platinum element located on the surface of the nanoparticles is also significantly improved due to the influence of the surface structure and electronic effects of the carbon carrier, so that the catalyst has both high ORR oxygen catalytic performance and good stability, which is of great significance for the large-scale production of catalysts and promoting the application of fuel cell technology.
[0009] In the present invention, the carrier of the low-platinum composite catalyst is a graphene activated carbon carrier rather than a traditional carbon carrier; the graphene activated carbon carrier is a transition metal Co-NCG oxygen reduction catalyst with an oxygen reduction reaction (ORR) active site, which can also be used as a carrier to replace the traditional commercial carbon carrier due to its good electrical conductivity and high specific surface area; and platinum also has oxygen reduction catalytic activity; the present invention realizes uniform loading of Pt particles on the graphene activated carbon carrier Co-NCG, combines the advantages of the two, and can further enhance the redox reaction performance of the catalyst.
[0010] The present invention provides a graphene active carbon-based material-supported low-platinum composite catalyst, the mass percentage composition of the catalyst is: graphene active carbon carrier Co-NCG: 90% to 95%, platinum: 5 to 10%. That is, the mass percentage of metal Pt in the catalyst is 5 to 10 wt%.
[0011] The present invention provides a method for preparing a graphene active carbon-based material-supported low-platinum composite catalyst, comprising the following steps: (1) The graphene raw material is emulsified and sheared in a methanol solution to make it fully refined and uniform, and zinc nitrate hexahydrate and cobalt nitrate hexahydrate are dissolved in the above-mentioned methanol solution in which the graphene is dispersed. The obtained solution is named solution A; the concentration of graphene in solution A is 0.1-1.2 mg / mL, the concentration of zinc nitrate hexahydrate in solution A is 2.4-115.2 mg / mL, and the molar ratio of zinc salt to cobalt salt is 2-8:1. (2) dissolving 2-methylimidazole in a methanol solution, and the obtained solution is named solution B; the molar ratio of zinc nitrate hexahydrate to dimethylimidazole is (0.5-1):(2-8), and the concentration of 2-methylimidazole in solution B is 20-90 mg / mL; (3) Add solution B to solution A under stirring conditions, and stir at room temperature to obtain a dark purple suspension. The obtained product is centrifuged, washed with ethanol three times, and vacuum dried to obtain the precursor Co@ZIF-8 / G; (4) The precursor Co@ZIF-8 / G was transferred to a porcelain boat and placed in a tube furnace for heat treatment to obtain the transition metal-doped ZIF-8-derived non-precious metal catalyst Co-NCG; (5) The prepared non-precious metal catalyst Co-NCG was ultrasonically dispersed in the polyol solution, and H 2 PtCl 6 Solution, oil bath heating reflux reduction Pt 4+ , so that the Pt particles are evenly loaded on the Co-NCG carrier, and then filtered, washed with anhydrous ethanol several times and dried to obtain the Pt / Co-NCG catalyst.
[0012] Furthermore, in the above steps (1) and (2), the molar ratio of zinc nitrate hexahydrate to cobalt nitrate hexahydrate is preferably 5:1; and the molar ratio of the zinc nitrate hexahydrate to dimethylimidazole is preferably (0.5-1):(2-6).
[0013] Furthermore, in the above step (4), the heat treatment conditions are: heating to 600-1200°C at a rate of 1-10°C per minute under a nitrogen atmosphere and keeping the temperature for 1-3h.
[0014] Furthermore, in the above step (5), the polyol is one of ethylene glycol, 2-propylene glycol or 1,4-butanediol; and the concentration of the non-precious metal catalyst Co-NCG ultrasonically dispersed in the polyol solution is 0.5~2 mg / mL.
[0015] Furthermore, in the above step (5), the time for ultrasonic dispersion of the Co-NCG in the polyol solution is 1-3 h, and the power of ultrasonic dispersion is 250-450W.
[0016] Furthermore, in the step (3), the stirring reaction time at room temperature is 1 to 3 h.
[0017] Furthermore, in the above step (5), the reflux heating temperature is 120°C to 150°C, and the reflux reaction time is 1 to 3 hours.
[0018] Furthermore, in the above step (5), H 2 PtCl 6 The concentration range of the solution is 0.005~0.02g / mL, and the non-precious metal catalyst and H 2 PtCl 6 The mass ratio is 3:1~10:1.
[0019] The present invention provides the application of the above-mentioned graphene activated carbon-based material-supported low-platinum composite catalyst in the cathode oxygen reduction process of a fuel cell. In this application, the graphene activated carbon-based material-supported low-platinum composite catalyst exhibits better oxygen reduction performance than commercial platinum-carbon catalysts, the acidic half-wave potential reaches 0.88V, and the catalyst also has good stability. This is of great significance for developing Pt-based catalysts with higher activity and stability and reducing the amount of Pt used in fuel cell stacks.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The preparation method of the low-platinum composite catalyst supported by graphene active carbon-based materials of the present invention, wherein the transition metal is Co compared to other transition metals, Co 3 + / Co 2 +The equilibrium potential is higher, and it is not easy to undergo Fenton-like reactions. It is not easy to dissolve in acidic media. The activated carbon carrier Co-NCG is prepared by high-temperature calcination of Co@ZIF-8 / G. This carbon carrier itself has active components and provides active sites. It also has excellent conductivity, large specific surface area and suitable pore volume structure. It can improve the overall performance of the catalyst through the electron transfer between the active components. Loading the precious metal Pt on this carrier can achieve the synergistic effect of precious metal catalysts and non-precious metal catalysts, thereby effectively improving the mass transfer and charge transfer efficiency and improving the electrochemical performance of the battery.
[0021] (2) The heteroatom-doped modified carbon support has stronger anchoring points and corrosion resistance to avoid the dissolution and separation of platinum. The modified carbon support Co-NCG provides a strong metal-support interaction and promotes the uniform distribution of Pt particles on it to avoid the migration and aggregation of a large number of Pt particles. In addition, the modified carbon support Co-NCG has strong anchoring points and higher graphitization, which also provides corrosion resistance, thereby achieving a long life cycle of the catalyst.
[0022] (3) Pt in the reduction solution of the present invention 4+ Compared with other reducing agents, the ethylene glycol used can be used as both a reaction solvent and a reducing agent without the need for adding a protective agent. It has a good complexation effect with platinum particles and carbon carriers, can prevent nanoparticles from agglomerating, and obtain uniform carbon-supported platinum nanoparticles. In addition, its raw materials are easily available, green and can be mass-produced.
[0023] (4) The raw materials used in the preparation method of the activated carbon-based material-supported low-platinum composite catalyst of the present invention are cheap and easily available, and the preparation method is simple and economical, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 X-ray diffraction (XRD) spectra of Co-NCG catalysts prepared at different calcination temperatures in Examples 1, 2, 3, and 4; Figure 2 X-ray diffraction (XRD) spectra of the Co-NCG-1000 catalyst prepared in Example 3 and the Pt / Co-NCG composite catalysts with different Pt contents prepared in Examples 5, 6, and 7; Figure 3 TEM image of the Co-NCG-1000 catalyst prepared in Example 3; Figure 4 Pt prepared in Example 6 10 Transmission electron microscopy TEM image of / Co-NCG catalyst; Figure 5 Pt prepared in Example 610 Ultra-high resolution transmission electron microscopy (HRTEM) image of / Co-NCG catalyst and Pt particle size distribution; Figure 6 The Co-NCG-1000 prepared in Example 3 and the Pt prepared in Example 6 10 / Raman comparison of Co-NCG catalysts; Figure 7 LSV curves of the oxygen reduction catalytic activity test of the Co-NCG-1000 catalyst prepared in Example 3 and the Pt / Co-NCG composite catalysts with different Pt contents prepared in Examples 5, 6, and 7, wherein the abscissa represents the voltage in volts (V); the ordinate represents the current density in mA / cm 2 ; Figure 8 Pt prepared in Example 6 10 LSV curves of oxygen reduction catalytic activity test of Pt / G, Pt / NC, Pt / Co-NCG catalyst, comparative examples 3, 4, 5 and commercial Pt / C, where the abscissa represents voltage in volts (V); the ordinate represents current density in mA / cm 2 ; Fig. 9 Pt 10 / Co-NCG in 0.1mol / L HClO 4 CV curve in electrolyte, where the horizontal axis represents voltage in volts (V); the vertical axis represents current density in mA / cm 2 ; Fig.10 Pt 10 Comparison of stability between Pt / C / Co-NCG and commercial Pt / C after 5000 ADTs cycles. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and technical effect of the embodiment of the present invention clearer, the technical solution in the embodiment of the present invention is clearly and completely described. It should be understood that the specific implementation methods described here are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0026] The present invention provides a method for preparing a low-platinum composite catalyst supported by a graphene active carbon-based material, the steps of which are as follows: The graphene raw material was emulsified and sheared in a methanol solution to make it fully refined and uniform. Zinc nitrate hexahydrate and cobalt nitrate hexahydrate were dissolved in the above-mentioned methanol solution in which graphene was dispersed, and the obtained solution was named solution A. 2-Methylimidazole was also dissolved in a methanol solution, and the obtained solution was named solution B. Solution B was added to solution A under stirring, and a black-purple suspension was obtained by stirring at room temperature. The obtained product was centrifuged, washed with ethanol three times, and vacuum dried to obtain the precursor Co@ZIF-8 / G. The precursor Co@ZIF-8 / G was transferred to a porcelain boat and placed in a tube furnace for heat treatment to obtain a transition metal-doped ZIF-8-derived non-precious metal catalyst Co-NCG. The prepared metal organic framework-derived carbon carrier Co-NCG was ultrasonically dispersed in a polyol solution, and H was added dropwise thereto. 2 PtCl 6 Solution, oil bath heating reflux reduction Pt 4+ , so that the Pt particles are evenly loaded on the Co-NCG carrier, and then filtered, washed with anhydrous ethanol several times and dried to obtain the Pt / Co-NCG catalyst.
[0027] As a preferred embodiment, the preparation method of the graphene raw material is an electrochemical exfoliation method. Furthermore, the graphene raw material is emulsified and sheared in a methanol solution for 2 hours.
[0028] Furthermore, the mixed solution A is prepared by adding 2.933-3.933 g of zinc nitrate hexahydrate and 0.586-1.586 g of cobalt nitrate hexahydrate into 100-300 mL of methanol; the mixed solution B is prepared by adding 5.489-7.489 g of 2-methylimidazole into 100-300 mL of methanol.
[0029] Furthermore, the stirring time at room temperature after adding the B solution to the A solution is 6 h.
[0030] Furthermore, the heat treatment conditions are: heating to 800-1100°C at a rate of 5°C per minute in a nitrogen atmosphere and keeping the temperature for 1 h.
[0031] Furthermore, the vacuum drying temperature is 60°C.
[0032] Furthermore, the added polyol solution is preferably ethylene glycol.
[0033] Furthermore, the amount of chloroplatinic acid solution added should make the mass fraction of platinum about 10wt%. If the platinum content is too high, it will need to be washed and removed multiple times, which is cumbersome. In addition, the high platinum content is easy to cause agglomeration in the activated carbon carrier dispersion solution. If the platinum content is too low, it is difficult to form enough platinum particles dispersed on the Co-NCG carrier, and more oxygen reduction active sites cannot be provided, which affects the catalytic performance of the obtained platinum-based catalyst. At the same time, it is not conducive to improving the stability of the catalyst.
[0034] Furthermore, after adding chloroplatinic acid, the stirring time at room temperature is 2 to 3 h.
[0035] Furthermore, the heating reflux temperature is 120-150° C., and the reflux reaction time is 1-3 h.
[0036] The present invention is further described in detail below in conjunction with specific examples, but the embodiments of the present invention are not limited thereto, and for process parameters not specifically noted, conventional techniques may be used. In order to enable the above-mentioned implementation details and operations of the present invention to be clearly understood by those skilled in the art, as well as the specific embodiment of the innovative nature of the preparation of the low-platinum composite catalyst supported by the activated carbon-based material of the present invention and the research on its catalytic performance, the above-mentioned technical scheme is illustrated below by multiple examples.
[0037] Comparative Example 1: Preparation of Co-NC catalyst: 2.933 g of zinc nitrate hexahydrate and 0.586 g of cobalt nitrate hexahydrate were added to 200 mL of methanol solution and recorded as solution A. 6.489 g of 2-methylimidazole was dissolved in 200 mL of methanol solution and stirred at room temperature for 30 min to form a clear and transparent solution, which was marked as solution B. Subsequently, solution B was slowly added to solution A and stirred at room temperature for 6 h. After stirring, it was washed with methanol three times to remove alcohol-soluble impurities and prevent sample agglomeration during the drying process. The obtained product was vacuum dried at 60 ° C for 12 h. The dried sample was transferred to a corundum porcelain boat with a lid and placed in a tube furnace at N 2 Under an inert gas protection atmosphere, the temperature was raised to 1000 °C at a heating rate of 5 °C / min and the pyrolysis process was carried out at a constant temperature for 1 h. The temperature was naturally cooled to obtain a product recorded as Co-NC.
[0038] Comparative Example 2: Preparation of NC Catalyst 2.933 g of zinc nitrate hexahydrate was added to 200 mL of methanol solution and recorded as solution A. 6.489 g of 2-methylimidazole was dissolved in 200 mL of methanol solution and stirred at room temperature for 30 min to form a clear and transparent solution, which was marked as solution B. Subsequently, solution B was slowly added to solution A and stirred at room temperature for 6 h. After stirring, it was washed with methanol three times to remove alcohol-soluble impurities and prevent sample agglomeration during the drying process. The obtained product was vacuum dried at 60 ° C for 12 h. The dried sample was transferred to a corundum porcelain boat with a lid and placed in a tube furnace at N 2 Under an inert gas atmosphere, the temperature was raised to 1000 °C at a heating rate of 5 °C / min and the pyrolysis process was carried out at a constant temperature for 1 h. The temperature was naturally cooled to obtain a product recorded as NC.
[0039] Comparative Example 3: Preparation of Pt / G catalyst 40 mg of pure graphene G prepared by electrochemical exfoliation was ultrasonically dispersed in 30 mL of ethylene glycol solution for 2 h, and then 1000 μL of 0.01 g / mL H 2 PtCl 6 The solution was stirred at room temperature for 3 h. The Pt 4+ , so that the Pt particles are loaded on the G carrier, and then filtered, washed with anhydrous ethanol three times and dried to obtain the Pt / G catalyst.
[0040] Comparative Example 4: Preparation of Pt / NC catalyst 40 mg of the organic framework MOF-derived carbon support NC prepared in Comparative Example 2 was ultrasonically dispersed in 30 mL of ethylene glycol solution for 1 h, and then 1000 μL of 0.01 g / mL H 2 PtCl 6 The solution was stirred at room temperature for 3 h. The Pt 4+ , so that the Pt particles are evenly loaded on the NC carrier, and then filtered, washed with anhydrous ethanol three times and dried to obtain the Pt / NC catalyst.
[0041] Comparative Example 5: Preparation of Pt / Co-NC Catalyst 40 mg of the metal organic framework-derived carbon support Co-NC without graphene prepared in Comparative Example 1 was ultrasonically dispersed in 45 mL of ethylene glycol solution for 1 h, and then 1000 μL of 0.01 g / mL H 2 PtCl 6 The solution was stirred at room temperature for 3 h. The Pt 4+, so that the Pt particles are uniformly loaded on the Co-NC carrier, and then filtered, washed with anhydrous ethanol 5 times and dried to obtain the Pt / Co-NC catalyst.
[0042] Example 1: Preparation of Co-NCG-800 catalyst carrier 60 mg of graphene raw material was emulsified and sheared in 200 mL of methanol solution for 2 h to make it fully refined and uniform. 2.933 g of zinc nitrate hexahydrate and 0.586 g of cobalt nitrate hexahydrate were added to the above methanol solution and recorded as solution A. The molar ratio of the added zinc nitrate hexahydrate and cobalt nitrate hexahydrate was 5:1. 6.489 g of 2-methylimidazole was dissolved in 200 mL of methanol solution and stirred at room temperature for 30 min to form a clear and transparent solution, which was marked as solution B. Subsequently, solution B was slowly added to solution A and stirred at room temperature for 6 h. After stirring, it was washed with methanol 3 times to wash away alcohol-soluble impurities and prevent sample agglomeration during the drying process. The obtained product was vacuum dried at 60 ° C for 12 h. The dried sample was transferred to a corundum porcelain boat with a lid, placed in a tube furnace, and heated at N 2 Under an inert gas protection atmosphere, the temperature was raised to 800 °C at a heating rate of 5 °C / min and the pyrolysis process was carried out at a constant temperature for 1 h. The temperature was naturally cooled to obtain a product recorded as Co-NCG-800.
[0043] Example 2: Preparation of Co-NCG-900 catalyst support The difference between this embodiment and embodiment 1 is that: this embodiment provides a method for preparing a graphene activated carbon carrier Co-NCG-900 oxygen reduction electrocatalyst, wherein the temperature is raised to 900° C. during heat treatment. The rest is the same as in embodiment 1.
[0044] Example 3: Preparation of Co-NCG-1000 catalyst carrier The difference between this embodiment and embodiment 1 is that: this embodiment provides a method for preparing a graphene activated carbon carrier Co-NCG-1000 oxygen reduction electrocatalyst, wherein the temperature is raised to 1000° C. during heat treatment. The rest is the same as in embodiment 1.
[0045] Example 4: Preparation of Co-NCG-1100 catalyst support The difference between this embodiment and embodiment 1 is that: this embodiment provides a method for preparing a graphene activated carbon carrier Co-NCG-900 oxygen reduction electrocatalyst, wherein the temperature is raised to 900° C. during heat treatment. The rest is the same as in embodiment 1.
[0046] According to the above scheme, the metal-organic framework compound MOF is synthesized by using materials such as transition metals, thereby realizing the synthesis of the metal-nitrogen co-doped porous carbon material precursor, so that the electrocatalyst has the oxygen reduction function while also having a large specific surface area and good thermal stability, thereby meeting the stability use requirements of the fuel cell; at the same time, the materials used in the entire electrocatalyst synthesis step are relatively common and inexpensive, and the synthesis steps are relatively simple, thereby making the production cost of the electrocatalyst low, which is conducive to industrial production and use.
[0047] Example 5: Pt 5 Preparation of Co-NCG catalyst 50 mg of the metal organic framework-derived carbon support Co-NCG prepared in Example 1 was ultrasonically dispersed in 25 mL of ethylene glycol solution for 1 h, and then 500 μL of 0.01 g / mL H 2 PtCl 6 The solution was stirred at room temperature for 2 h. The Pt 4+ , so that the Pt particles are uniformly loaded on the Co-NCG carrier, and then filtered, washed with anhydrous ethanol twice and dried to obtain Pt 5 / Co-NCG catalyst.
[0048] Example 6: Pt 10 Preparation of Co-NCG catalyst 40 mg of the metal organic framework-derived carbon support Co-NCG prepared in Example 1 was ultrasonically dispersed in 30 mL of ethylene glycol solution for 1 h, and then 1000 μL of 0.01 g / mL H 2 PtCl 6 The solution was stirred at room temperature for 3 h. The Pt 4+ , so that the Pt particles are uniformly loaded on the Co-NCG carrier, and then filtered, washed with anhydrous ethanol three times and dried to obtain Pt 10 / Co-NCG catalyst.
[0049] Example 7: Pt 20 Preparation of Co-NCG catalyst 40 mg of the metal organic framework-derived carbon support Co-NCG prepared in Example 1 was ultrasonically dispersed in 45 mL of ethylene glycol solution for 2 h, and then 2000 μL of 0.01 g / mL H 2 PtCl 6 The solution was stirred at room temperature for 3 h. The Pt 4+, so that the Pt particles are uniformly loaded on the Co-NCG carrier, and then filtered, washed with anhydrous ethanol for 5 times, and dried to obtain Pt 20 / Co-NCG catalyst.
[0050] Example 8: Pt 7 Preparation of Co-NCG catalyst 50 mg of the metal organic framework-derived carbon support Co-NCG prepared in Example 1 was ultrasonically dispersed in 25 mL of ethylene glycol solution for 1 h, and then 700 μL of 0.01 g / mL H 2 PtCl 6 The solution was stirred at room temperature for 2 h. The Pt 4+ , so that the Pt particles are uniformly loaded on the Co-NCG carrier, and then filtered, washed with anhydrous ethanol twice and dried to obtain Pt 7 / Co-NCG catalyst.
[0051] Example 9: X-ray diffraction analysis The Co-NC, Co-NCG and Pt / Co-NCG prepared in the present invention are subjected to X-ray diffraction respectively, and the diffraction patterns thereof are analyzed. Figure 1 The X-ray diffraction (XRD) spectra of the Co-NCG catalysts prepared at different calcination temperatures in Examples 1, 2, 3, and 4. It can be seen from the figure that the phase composition of the catalyst material at different calcination temperatures is basically consistent with the characteristic peaks of the graphene raw material, and the crystal form is best maintained when the calcination temperature is 1000°C. Figure 2 The X-ray diffraction (XRD) spectra of the Co-NCG catalyst prepared in Example 3 and the Pt / Co-NCG composite catalysts with different Pt contents prepared in Examples 5, 6, and 7 show that the prepared samples have characteristic peaks at 39.763°, 46.243°, and 67.454°. By comparing the standard card PDF#04-0802, it can be seen that they correspond to the (111), (200), and (220) crystal planes of face-centered cubic Pt, respectively. It can be seen that with the increase of Pt content, the degree of crystallization of Pt particles is good. Pt is calculated by Scherrer formula 10 The Pt particle size in / Co-NC is about 3.2 nm, which is consistent with the catalyst particle size results obtained from randomly measured nanoparticles in TEM images.
[0052] Example 10: Electron Microscope Analysis The products prepared by the present invention are respectively analyzed by electron microscope to obtain corresponding TEM and particle size distribution images of Pt particles.
[0053] Figure 3The TEM image of Co-NCG-1000 prepared in Example 3 shows a rhombic dodecahedron structure with a certain degree of depression, which is mainly caused by the decomposition of organic ligands in the skeleton and the evaporation of metal elements during the high-temperature carbonization process. Its particle size is relatively small, about 30 nm, and it can be evenly dispersed on the graphene surface.
[0054] Figure 4 Pt prepared in Example 6 10 The transmission electron microscopy (TEM) image of the Pt / Co-NCG catalyst shows that the Pt particles can be uniformly loaded on the surface of the carbon support Co-NCG.
[0055] Figure 5 Pt prepared in Example 6 10 High-resolution transmission electron microscopy (HRTEM) image of the / Co-NCG catalyst and the particle size distribution diagram of Pt particles. The image shows that the Pt particles can be evenly distributed on the carbon support Co-NCG and their average particle size is about 2.8 nm.
[0056] Example 11: Catalyst structure analysis Figure 6 The Co-NCG-1000 prepared in Example 3 of the present invention and the Pt prepared in Example 6 10 Raman spectra of the two materials / Co-NCG. Both samples show two characteristic peaks, one of which is at about 1343 cm -1 The peak that appears represents the D band of carbon materials, which is around 1590 cm -1 The peaks that appear represent the G bands of carbon materials. The strength of the D band represents the structural defects and disorder of the carbon material, and the G band represents the sp 2 Domain E 2g vibration. The intensity ratio of the D band to the G band (I D / I G ) is used to estimate the disorder and defect level of carbon materials. Figure 8 It is shown that the disorder and defects of the catalyst increase after Pt particles are loaded.
[0057] In order to further illustrate that the present invention can achieve the technical effect, the following experiments are performed: Example 12: ORR performance test The electrochemical analysis test uses a CHI760E electrochemical workstation and a traditional three-electrode (working electrode, reference electrode, counter electrode) measurement system. The working electrode is a disc glassy carbon electrode modified with a catalyst, the reference electrode uses an Ag / AgCl electrode containing a saturated KCl solution, and the counter electrode uses a carbon rod electrode. The test needs to be done in advance with 0.1M HClO 4 O is introduced into the electrolyte2 or N 2 , so that the electrolyte contains saturated O 2 or N 2 .
[0058] Preparation of working electrode: First, polish the glassy carbon RDE with 0.05 μm alumina polishing paste and rinse with ultrapure water at least 3 times. To avoid contamination from the surrounding atmosphere, the polished electrode surface is sealed with ultrapure water. Add detergent to the electrolytic cell and brush it, rinse it with at least 1L of tap water, and then rinse it with 1L of ultrapure water. Before the electrochemical test, use freshly prepared 0.1 mol / L HClO 4 The electrolytic cell was rinsed with the solution (about 300 mL) three times. The working electrode was prepared by the ink method. The specific process is: accurately weigh 5 mg of the target catalyst and transfer it to a 2 mL centrifuge tube, add 645 μL of ultrapure water, 325 μL of isopropanol and 30 μL of 5wt% Nafion solution to the centrifuge tube to prepare the catalyst slurry, ultrasonically mix for more than 60 min to form a uniformly dispersed ink solution. Use a 20 μL pipette to accurately transfer an appropriate volume of solution and evenly apply it to the polished and cleaned working electrode surface, and dry it at room temperature to form a thin film working electrode.
[0059] Cyclic voltammetry: Cyclic voltammetry (CV) is a method of controlling the voltage of the working electrode to change in an isosceles triangle waveform so that oxidation and reduction reactions can occur alternately, while recording the current-voltage curve. It is often used to study the properties of electrode reactions, reaction mechanisms, and kinetic parameters of electrode processes. In the cyclic voltammetry test of this technical solution, the potential scanning rate is 50 mV / S, and the potential scanning range is 0.2~1.0 V vs. RHE). First, N 2 Saturated electrolyte test, then in O 2 To ensure that the gas is saturated, the target gas is passed through the electrolyte for at least 30 min before each test. 2 and O 2 The CV diagram in the figure is used to roughly evaluate the oxygen reduction performance of the catalyst.
[0060] Linear Sweep Voltammetry: Linear Sweep Voltammetry (LSV) refers to controlling the electrode voltage to change continuously and linearly while measuring the current response on the working electrode. In oxygen reduction catalyst testing, linear sweep voltammetry is usually used in combination with rotating disk electrode technology. From the linear sweep voltammetry curve, the oxygen reduction starting potential, half-wave potential, and limiting diffusion current density can be read. These are important parameters for evaluating the activity of oxygen reduction catalysts. In this technical solution, the starting point of catalyst oxygen reduction is defined as the oxygen reduction current density reaching 0.1 mAcm -2 The corresponding potential. Figure 7 In the diagram, the horizontal axis E / V represents the voltage in volts (V); the vertical axis Current Density represents the current density in mA / cm 2 ). The test results show that the loading of Pt particles can significantly improve the ORR activity of the catalyst, and when the mass fraction of Pt is 10wt%, the oxygen reduction performance reaches the best.
[0061] Example 13: Electrochemical oxygen reduction (RDE) test Accurately weigh 5 mg Pt 10 The Pt / Co-NCG catalyst was dispersed in 645 μL ultrapure water, 325 μL isopropanol and 30 μL 5 wt% Nafion solution. After ultrasonic dispersion, 20 μL (5 μL for Pt / C) was transferred and dropped on the surface of the glassy carbon electrode. After drying at room temperature, the catalyst electrode was obtained. The loading amount of the catalyst electrode was 0.510 mg / cm 2 The Pt 10 / Co-NCG samples were tested for oxygen reduction activity. The oxygen reduction scan rate was 10 mV / s and the electrolyte was O 2 and N 2 Saturated 0.1M HClO 4 Aqueous solution, potential window is 1.0 ~ 0V (vs. RHE). The obtained catalyst Pt 10 / Co-NCG was used as the working electrode, graphite as the counter electrode, and Ag / AgCl as the reference electrode. 2 and N 2 Saturated 0.1M HClO 4 The oxygen reduction activity of aqueous solution, in which N 2 The test is to subtract other background of catalyst.
[0062] Example 14: Cyclic Voltammetry Test (CV) The test was carried out under a three-electrode system (electrochemical workstation, Shanghai Huachen CHI604E) using Ag / AgCl electrode as the reference electrode, graphite as the auxiliary (counter) electrode, and glassy carbon electrode as the working electrode. The electrolyte was 0.1 M HClO 4 Aqueous solution, all tests were carried out at room temperature. The electrochemically active surface area of the catalyst was calculated from the measured cyclic voltammogram. Pt is a single molecule adsorption area of hydrogen in the potential range of 0~0.37 V (VS RHE). Based on this theory, the effective electrochemically active area (ESCA) of Pt can be indirectly calculated. The surface adsorption charge of Pt is 210 μC cm -2 . In calculating the adsorption charge Q H The hydrogen desorption area needs to be calculated in the process, and then the electrochemical active surface area ECSA (m 2 g -1 ) calculation formula to calculate:
[0063] M pt is the mass of Pt in the working electrode, K=210 μC cm -2 is the charge constant required for saturated adsorption of a single layer on the Pt surface. The CV curve obtained by the test is shown in Fig. 9 . Fig. 9 In the diagram, the horizontal axis E / V represents the voltage, in volts V; the vertical axis Currentdensity represents the current density, in mA cm -2 The test results show that ECSA = 127.52m 2 / g Pt .
[0064] Example 15: Electrochemical Accelerated Stability (ADT) Test Accurately weigh 5 mg of Pt prepared in Example 6 10 / Co-NCG catalyst and 20% commercial Pt / C catalyst were dispersed in 645μL ultrapure water, 325μL isopropanol and 30μL 5wt% Nafion solution. After ultrasonic dispersion, 20μL (5μL for Pt / C) was transferred and dropped on the surface of glassy carbon electrode. After drying at room temperature, the catalyst electrode was obtained. The loading amount of the catalyst electrode was 0.510mg / cm 2 The Pt 10 / Co-NCG samples and 20% commercial Pt / C catalysts were tested for oxygen reduction activity. The oxygen reduction scan rate was 10 mV / s and the electrolyte was O 2 and N 2 Saturated 0.1M HClO 4Aqueous solution, potential window is 1.0~0V (vs.RHE). The scan rate of 5000 cycles of potential cycling test is 100mV / s, the electrolyte is O 2 0.1 M HClO 4 aqueous solution, the potential window is 1.0~0.6V(vs.RHE) with the obtained catalyst Pt 10 / Co-NCG and commercial Pt / C catalyst electrodes were used as working electrodes, graphite was used as counter electrode, and Ag / AgCl was used as reference electrode. Fig.10 After 5000 ADTs cycles, Pt 10 The Si / Co-NCG catalyst showed excellent stability with a half-wave potential decay of only 6 mV, compared to a 36 mV loss in half-wave potential of the commercial Pt-C catalyst after 5000 ADTs cycles.
[0065] Example 16: Chronoamperometric (it) test Accurately weigh 5 mg Pt 10 / Co-NCG catalyst and 20% commercial Pt / C catalyst were dispersed in 645μL ultrapure water, 325μL isopropanol and 30μL 5wt% Nafion solution. After ultrasonic dispersion, 20μL (5μL for Pt / C) was transferred and dropped on the surface of glassy carbon electrode. After drying at room temperature, the catalyst electrode was obtained. The loading amount of the catalyst electrode was 0.510mg / cm 2 The Pt 10 The chronoamperometric test was performed on the Pt / Co-NCG catalyst sample and the 20% commercial Pt / C catalyst, where the test voltage was fixed at 0.7 V (vs. RHE), the rotation speed was 400 rpm, the test time was 40000 s, and the electrolyte was O 2 Saturated 0.1M HClO 4 The aqueous solution was Pt 10 / Co-NCG catalyst and commercial Pt / C catalyst electrode were used as working electrodes, graphite as counter electrode, and Ag / AgCl as reference electrode. The experimental results showed that the current density of commercial Pt / C decayed by 22% after 40,000s, and the current density of Pt / C decreased by 1.3%. 10 / Co-NCG current density only decays by 4%.
[0066] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A graphene activated carbon-based material loaded with low platinum catalyst, characterized in that: The mass percentage composition of the catalyst is: graphene active carbon carrier: 90% to 95%, platinum: 5 to 10%.
2. A method for preparing a graphene active carbon-based material-supported low-platinum catalyst according to claim 1, characterized in that The following steps are involved: (1) emulsifying and shearing the graphene raw material in a methanol solution to make it fully refined and uniform, dissolving zinc nitrate hexahydrate and cobalt nitrate hexahydrate in the above-mentioned methanol solution in which the graphene is dispersed, and the obtained solution is named solution A; (2) Dissolve 2-methylimidazole in methanol solution. The resulting solution is named solution B. (3) Add solution B to solution A under stirring conditions, and stir at room temperature to obtain a dark purple suspension. The obtained product is centrifuged, washed with ethanol three times, and vacuum dried to obtain the precursor Co@ZIF-8 / G; (4) The precursor Co@ZIF-8 / G was transferred to a porcelain boat and placed in a tube furnace for heat treatment to obtain the transition metal-doped ZIF-8-derived non-precious metal catalyst Co-NCG; (5) The prepared non-precious metal catalyst Co-NCG was ultrasonically dispersed in the polyol, and then H2PtCl6 solution was added dropwise, and the Pt was reduced by heating under reflux in an oil bath. 4+ , so that the Pt particles are evenly loaded on the Co-NCG carrier, and then filtered, washed with anhydrous ethanol several times and dried to obtain the Pt / Co-NCG catalyst.
3. The method for preparing a graphene active carbon-based material-supported low-platinum catalyst according to claim 2, characterized in that: In step (1), the concentration of graphene in solution A is 0.1-1.2 mg / mL, the concentration of zinc nitrate hexahydrate in solution A is 2.4-115.2 mg / mL, and the molar ratio of zinc nitrate hexahydrate to cobalt nitrate hexahydrate is 2-8:
1.
4. The method for preparing a graphene active carbon-based material-supported low-platinum catalyst according to claim 2, characterized in that: The concentration of 2-methylimidazole in the solution B of step (2) is 20-90 mg / mL; the molar ratio of zinc nitrate hexahydrate to dimethylimidazole is (0.5-1):(2-8).
5. The method for preparing a graphene active carbon-based material-supported low-platinum catalyst according to claim 2, characterized in that: The stirring reaction time at room temperature in step (3) is 1 to 3 h.
6. The method for preparing a low-platinum catalyst supported by a graphene-activated carbon-based material according to claim 2, characterized in that: In step (4), the heat treatment conditions are: heating to 600-1200°C at a rate of 1-10°C per minute in a nitrogen atmosphere and keeping the temperature for 1-3 hours.
7. The method for preparing a graphene active carbon-based material-supported low-platinum catalyst according to claim 2, characterized in that: In step (5), the polyol is one of ethylene glycol, 2-propylene glycol or 1,4-butanediol; and the concentration of the non-precious metal catalyst Co-NCG ultrasonically dispersed in the polyol solution is 0.5-2 mg / mL.
8. The method for preparing a low-platinum catalyst supported by graphene active carbon-based materials according to claim 2, characterized in that: In step (5), the Co-NCG is ultrasonically dispersed in the polyol solution for 1 to 3 h, the ultrasonic dispersion power is 250 to 450 W, the reflux heating temperature is 120°C to 150°C, and the reflux reaction time is 1 to 3 h.
9. The method for preparing a low-platinum catalyst supported by a graphene active carbon-based material according to claim 2, characterized in that: In step (5), the concentration range of the H2PtCl6 solution is 0.005~0.02g / mL, and the mass ratio of the non-precious metal catalyst Co-NCG to H2PtCl6 is 3~10:
1.
10. Use of the graphene activated carbon-based material loaded with a low-platinum catalyst as claimed in claim 1 in a cathode oxygen reduction process of a fuel cell.
Citation Information
Cited By
Nb-oxygen fluorine cluster confinement and pulse induction ordering-based oxygen reduction catalyst and preparation method and application thereof
CN122025676A